Does Gender Equality in Labor Participation Bring Real Equality? Evidence from Developed and Developing Countries - Alfani, Federica; Clementi, Fabio; Fabiani, Michele; Molini, Vasco; Valentini, Enzo (World Bank, Washington, DC, 2021)
Drawing on various macro- and micro-data sources, the authors present robust evidence of an inverted U-shaped relationship between female labor force participation and inequality. Overall, female labor force participation is found to have a strong and significant dis-equalizing impact in at least three groups of developing countries with relatively low initial levels of participation. A decile-level analysis shows that female labor force participation has higher levels of returns among top deciles compared with the lower deciles in the developing countries analyzed. This evidence focuses attention on the importance of developing policies specifically targeting women in lower deciles of the income distribution.